Rural tourism demand of international visitors to the Kilim Karst Geoforest Park, Langkawi, Malaysia - Matthew, Nitanan Koshy (2014)
Rural tourism provides opportunities for visitors to visit rural attractions available in a rural area. Kilim Karst Geoforest Park (KKGP) which is located in a rural setting offers rural tourism experience to visitors. It is chosen as the study site in the present study because it is one of the three parks located in the Langkawi Island that has been granted geopark status by the United Nations Educational, Scientific, and Cultural Organization in 2007. The high number of international visitor arrivals to the park has induced the need to identify the factors influencing their visitations to the park. Besides that, whether the visitors to the park obtain benefits from their visit is unknown. And, the intangibility nature of the products and services offered at the park has necessitated the need to determine the economic value of the park. The objective of the study is to identify the socio-demographic and characteristics of visits of international visitors. Besides, to identify the factors influencing the rural tourism demand of international visitors to the Kilim Karst Geoforest Park, Langkawi and to determine the economic value of the park. Rural tourism demand model for the park has been developed using one of the popular environmental valuation techniques which is the Travel Cost Method. Both types of TCM methods the zonal and individual travel cost (ZTCM, ITCM) have been utilized in the study. The differences between the two methods are, for ZTCM demand is based from the particular zones, whereas for ITCM, it is based from the individuals who have visited the site only. The modification of the basic TCM model has taken into account other demand shifting variables besides the travel cost in the model. This is to overcome the problem of either underestimating or overestimating of the consumer surplus. The variables are onsite cost and time, cost to alternative site, quality of site, WTP and socio demographic variables constituting of age, gender, education level, and gross monthly income of the visitors. Structured questionnaire and face-to-face data collection method are employed to obtain the primary data from 330 international visitors for two weeks at the park and Langkawi international airport. The respondents are chosen based on the convenient sampling technique. However, only 300 samples are used for further analysis due to inadequate information accumulated from the respondents. In terms of choosing appropriate individual as respondent, guidelines are adhered to. Firstly, international visitors are asked about their nationality. This is because there is a major confusion in identifying whether the visitors are local or international visitors particularly visitors from China, Korea, Japan, India, and Indonesia. Besides, only the head of the group is selected as the respondent to avoid double counting of respondents. Average time incurred for the survey is about 10 – 15 minutes. There are six main elements in the designed questionnaire namely the record item, travel information, travel and on-site cost, quality of the site, willingness to pay (WTP) and finally, socio – demographic information. The instrument of study; the questionnaire is designed only in the English language. The reason is that the English language is an internationally recognized language. Hence, it will be a good medium to obtain higher response rate from the respondents. The Poisson regression analysis is conducted to estimate the ITCM model using the Limited Dependent models (LIMDEP) software, version 4. On the other hand, the Ordinary, Least Square (OLS) regression analysis is conducted for the ZTCM models using the Statistical Package for Social Science (SPSS), version 21. The findings show that for ZTCM, the economic value is estimated to be at €64 million using the Kilim hour’s model. On the other hand, the economic value for the Langkawi and Kilim satisfaction model could not be determined because the travel cost variable is found to be insignificant. For ITCM, the economic value is estimated to be at €296 million, €82 million, and €27 million for Langkawi, Kilim satisfaction and hour’s models respectively. The findings of the study will be useful for the management of the park to make any justifications regarding the spending for the park and in making appropriate decisions concerning to the development of the rural tourism in the park.